2018
DOI: 10.1016/j.genhosppsych.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

An innovative model to coordinate healthcare and social services for people with serious mental illness: A mixed-methods case study of Maryland's Medicaid health home program

Abstract: Maryland's psychiatric rehabilitation-based health home is a promising model for integration of behavioral, somatic, and social services for people with SMI but may be strengthened by additional policy and implementation supports, including incentives for external providers to engage in care coordination with health home providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 55 publications
1
56
0
Order By: Relevance
“…In addition to the 5 unique articles identified in the initial search strategy, 4 additional studies were identified through reference lists. Of the nine articles, 4 were peer-reviewed studies (Annamalai, Tek, Sernyak, Cole, & Steiner, 2016;Maragakis & RachBeisel, 2015;McGinty et al, 2018;Scharf et al, 2013), 3 were gray literature reports from non-profit public policy research organizations (Golembieweski et al, 2015;Scharf, Breslau, et al, 2014;Scharf, Eberhart, et al, 2014), and 2 were gray literature reports from state Medicaid programs (Health Services Advisory Group, 2015; Missouri HealthNet, 2017).…”
Section: Implementation Barriers and Facilitatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the 5 unique articles identified in the initial search strategy, 4 additional studies were identified through reference lists. Of the nine articles, 4 were peer-reviewed studies (Annamalai, Tek, Sernyak, Cole, & Steiner, 2016;Maragakis & RachBeisel, 2015;McGinty et al, 2018;Scharf et al, 2013), 3 were gray literature reports from non-profit public policy research organizations (Golembieweski et al, 2015;Scharf, Breslau, et al, 2014;Scharf, Eberhart, et al, 2014), and 2 were gray literature reports from state Medicaid programs (Health Services Advisory Group, 2015; Missouri HealthNet, 2017).…”
Section: Implementation Barriers and Facilitatorsmentioning
confidence: 99%
“…Study characteristics-Seven studies examined implementation of BHHs at multiple sites, of which two occurred across multiple states (Scharf, Eberhart, et al, 2014; and five occurred in single states (Golembieweski et al, 2015;Health Services Advisory Group, 2015;McGinty et al, 2018;Missouri HealthNet, 2017;Scharf, Breslau, et al, 2014) (Table 3). Two studies looked at implementation at single sites (Annamalai et al, 2016;Maragakis & RachBeisel, 2015).…”
Section: Implementation Barriers and Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examine only the early effects of HHs. HHs involve complex implementation activities, such as establishing coordinated relationships between specialty behavioral and general medical care providers (McGinty et al, 2018). Thus, effects may vary over time.…”
Section: Discussionmentioning
confidence: 99%
“…Other research that has also been done is research by Mcginty (2017) into the provision of nursing care in the form of a combination of sole specialist nursing actions that are CBT in patients, FPE in the family, supportive therapy for the group, and the implementation of care by cadres to improve self-sufficiency of patients with chronically low selfesteem, and can provide significant change. This empowers families here through FPE while in research, one component of FPE is called family empowerment (Stolzenburg, 2017).…”
Section: Introductionmentioning
confidence: 99%